Studies of the chemical functionalisation of diamond electrodes - Foord, J; Hao, W; Hurst, S (2007)
Physical and chemical adsorption routes which have been established for more conventional carbon electrode materials have been examined for the surface chemical modification of diamond electrodes. The deposition of a range of anthracene-substituted and anthroquinone species has been examined using photoelectron spectroscopic and electrochemical methods. Whilst physical adsorption of the species studied is easily achieved, the stability of the adlayers is much less on diamond than on typical carbon electrodes, so the surface modifier is lost to the solution phase. In contrast covalent binding of anthroquinone to the diamond surface results in a stable functionalised electrode. It is demonstrated that catalytic oxygen reduction and pH sensitive electrochemistry are introduced in this way. © 2007 Elsevier B.V. All rights reserved.